Physiochemical properties of Sarawak's adapted Liberica coffee silverskin utilizing varying solvents - Nick Laurence, Buyong; Elexson, Nillian (Wiley Periodicals LLC., 2023)
This study aimed to investigate the physiochemical properties of Sarawak's adapted Liberica coffee silverskin (CS) using multiple solvents (distilled water, methanol, and ethanol) and its impact on the total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activities of the CS. The results showed that the highest TPC was observed in the methanol extract (15.24 ± 0.65 mg GAE/g), while the highest TFC was recorded when extracted with ethanol (25.14 ± 0.59 mg QE/g). The DPPH activity was also found to be highest in the ethanol extract (83.85 ± 1.78%), concurred by the results in the FRAP assay as the highest reduction was also in ethanol (11.40 ± 18.57 μmol FSE/g). These findings demonstrate that the bioactive compounds of CS extracted can be greatly influenced by the choice of solvent while highlighting the potential for Sarawak's adapted Liberica CS to be further harnessed into a valueadded product and enabling a better by-product waste management.